URGENCY CORPORATE SOCIAL RESPONSIBILITY (CSR) TOWARDS CORPORATE DEVELOPMENT IN INDONESIA - Garaika, Garaika (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The implementation of Corporate Social Responsibility / CSR carried out by a company is an urgent action towards the development of a company in Indonesia, this proves that a company is said to be good, if in carrying out its activities not only seek profit but also have an obligation to carry out its social responsibilities. In implementing CSR, there is a lot that can be done by companies in improving the welfare of the community, for example making public facilities, giving scholarships to students who have long-term goals. In reality there are still many companies that do not realize the importance of CSR, so there are still companies that have not implemented it. CSR is very beneficial for the company if implemented because a company will develop rapidly and sustainably if it always maintains relations with the community. So that the implementation of CSR is so urgent for the development of companies in Indonesia. Keywords: Urgency, Corporate Social Responsibility, company